Nutrient Dynamics and Phytoplankton Communities in Coastal Ecosystems of Lamongan, Indonesia - A'yun, Qurrota; Nabilah, Mariah; Asadi, Muhammad Arif; Yona, Defri; Aliviyanti, Dian (Water and Marine Pollution Journal: PoluSea, 2025)
Coastal waters are critical transition zones sensitive to both natural processes and anthropogenic pressures. Lamongan’s coastal waters, especially around Paciran and Brondong, have undergone increasing nutrient stress due to expanding fisheries and tourism. This study aimed to assess how key water quality parameters (temperature, salinity, dissolved oxygen, nitrate, and phosphate) shape phytoplankton abundance and community structure in Paciran and Brondong, Lamongan Regency, Indonesia. Data were collected from four stations over three sampling campaigns between May and July 2023, with each campaign separated by approximately two weeks. A total of 12 water samples were analyzed for nutrient concentrations and phytoplankton composition, employing standardized water sampling and microscopic identification of phytoplankton genera. Physicochemical parameters were measured in situ, while nutrient analyses were conducted in the laboratory using spectrophotometry. Ecological indices and statistical modeling were then applied to elucidate driving factors. Results show that elevated nitrate and warm temperatures corresponded with higher phytoplankton abundance, predominantly Diatoms. Chaetoceros emerged as the dominant genus, indicating eutrophic tendencies and aligning with observations in similarly impacted coastal areas. Despite moderate overall diversity, the clear correlation between nutrient enrichment and Chaetoceros proliferation underscores the risk of future harmful algal blooms under unchecked anthropogenic inputs. These findings confirm that the interplay of nutrient loading, temperature regimes, and localized hydrodynamics critically influences primary productivity in tropical coastal waters. In summary, this study highlights the vulnerability of Paciran and Brondong waters to eutrophication driven primarily by excessive nitrogen. The implications extend to resource management and conservation, suggesting that multi-nutrient control and proactive monitoring of diatom dominance are essential to sustaining ecological balance. By providing empirical evidence on critical drivers of phytoplankton dynamics, the research supports informed decision-making to mitigate negative impacts on marine ecosystems and local livelihoods.